A Plausible Anti-Apoptotic Role of Up-Regulated OCT4B1 in Bladder Tumors - Asadzadeh, Jamshid; Asadi, Malek Hossein; Shakhssalim, Nasser; Rafiee, Mahmoud-Reza; Kalhor, Hamid Reza; Tavallaei, Mahmoud; Mowla, Seyed Javad (Urology Journal, 2012)
PURPOSE: To investigate and compare the expression of OCT4B1 between tumor and non-tumor bladder tissues. MATERIALS AND METHODS: We investigated the expression of OCT4B1 in 30 tumor and non-tumor surgical specimens of the bladder, using the TaqMan real-time polymerase chain reaction approach and by carefully designing primers and probes specific for the amplification of the variant. RESULTS: Most tumor and non-tumor samples of the bladder showed OCT4B1 expression, but its expression level was significantly higher in the tumors (P < .002). Moreover, the up-regulation of OCT4B1 was more significant in high-grade tumors compared to the low-grade ones (P < .05). We have also employed the RNA interference strategy to evaluate the functional role of OCT4B1 in a bladder cancer cell line, 5637. Suppression of OCT4B1 caused some changes in cell cycle distribution, and significantly elevated the rate of apoptosis in the cells. CONCLUSION: Our findings suggest that OCT4B1 plays a potential role in tumor initiation and/or progression of the bladder cancer. Additionally, OCT4B1 can be regarded as a new tumor marker for detection, classification, and treatment of the bladder cancer. However, more experimental studies are needed to replicate our findings.